Incentives, Motivation, and Performance of Teachers at North Jakarta - Dewi Yuliyanti; Bedjo Sudjanto; Heru Santosa (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
The article aimed to find out how much the influence of incentives and motivation on the performance of teachers at Madrasah Ibtidaiyah Swasta in North Jakarta City. This article used survey method with quantitative approach by using path analysis technique with signification rate of 0.05 (5%). In collecting data the researchers used questionnaire. Questionnaires were distributed online (in the form of google form) using tokens to respondents to obtain data on all variables studied which included incentives, work motivation, and performance variables. The survey involved 84 teachers as samples using the cluster random sampling technique. The results showed that there was a direct positive influence of incentives on teacher performance, there wa a direct positive influence of motivation on teacher performance, and there was a direct influence of incentives on motivation. Keywords: Incentive Teachers, Teachers Moativation, Teachers Performance